From The Gongola to The Forcados: Colonial Water Transport and Economic Development In Nigeria - Bello, Muhammad A.; Ya’u, Usman Isah (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
In the course of European imperial expansion, movement was done through rivers to penetrate the interior of Africa and establish colonial rule, thereby promoting commercial and industrial development at the expense of Africans. Following the British imperial penetration of the Nigerian area and the military conquest of its peoples, they utilized navigable rivers from the South to the North in the transportation of goods and services to a number of port-towns for redistribution and consumption in the hinterland. European manufactured goods were brought to the Nigerian coastal areas, including Burutu, one of the major ports through which goods were imported and evacuated by cargo ships. Through Burutu port on the Forcados River in the Niger Delta, large quantities of imported goods were transported by ships to Lokoja on the Niger River, Makurdi and Numan on the Benue River, to Nafada and Dadin Kowa ports on the Gongola River. At the same time, large tons of agricultural and forest products were exported through the same waterway. This paper, which is based largely on the use of archival records, examines the process of the utilization of the Gongola River flood waters in Northern Nigeria in the colonial water transportation of goods and services to the Forcados River in Southern Nigeria, thereby facilitating the process of the economic development of the country.